MUSLIM CONSUMER TRUST IN SHARIA-COMPLIANT PRODUCT: A SYSTEMATIC LITERATURE AND CONCEPTUAL REVIEW WITHIN ISLAMIC ECONOMIC PERSPECTIVES - Mela Listi Rohmawati (SHACRAL: Shari'ah Economics Review Journal, 2025)
Muslim consumer trust in sharia-compliant products plays a crucial role in the development and sustainability of the Islamic economy. As the global Muslim population continues to grow, demand for products that comply with Islamic principles particularly halal and ethically produced goods has increased significantly. Trust becomes a central issue because Muslim consumers are required not only to consider functional product attributes but also religious compliance, ethical values, and institutional credibility. This study aims to examine the concept of Muslim consumer trust in sharia-compliant products through a systematic and conceptual literature review without employing primary data. Using a qualitative systematic literature review approach, this article synthesizes findings from prior national and international studies on Islamic consumer behavior, halal certification, sharia compliance, and trust theory. The review reveals that Muslim consumer trust is shaped by multiple interrelated dimensions, including halal certification credibility, perceived product quality aligned with the concept of halalan thayyiban, Islamic ethical branding, and institutional assurance from regulatory bodies. Empirical evidence from previous studies consistently demonstrates that halal certification and perceived sharia compliance reduce consumer uncertainty and perceived risk, thereby strengthening trust and increasing purchase intention and loyalty. In the Indonesian context, trust in sharia-compliant products is further reinforced by regulatory frameworks such as mandatory halal certification and the increasing role of government-authorized institutions in halal assurance. However, challenges remain, including uneven halal literacy, limited transparency in supply chains, and variations in consumer interpretation of sharia compliance across product categories. This article contributes theoretically by integrating trust theory with Islamic economic principles and offers a comprehensive conceptual framework for understanding Muslim consumer trust in sharia-compliant products. Practically, the findings provide insights for policymakers and industry practitioners to enhance trust through credible certification systems, transparent communication, and value-based marketing strategies consistent with Islamic ethic